2016
DOI: 10.5902/1980509821120
|View full text |Cite
|
Sign up to set email alerts
|

Substratos E Temperaturas Para Teste De Germinação Em Sementes De Myrtaceae

Abstract: RESUMOAs espécies brasileiras de Myrtaceae compreendem diversas plantas arbóreas e arbustivas que podem ser utilizadas na produção de frutos para consumo in natura ou para industrialização. Informações sobre avaliação da qualidade de sementes dessas espécies não estão bem definidas, principalmente as relacionadas à adequação do teste de germinação. Objetivou-se testar substratos e temperaturas para realização do teste de germinação em sementes ABSTRACTThe Brazilian species of the Myrtaceae comprises several a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 1 publication
4
22
0
11
Order By: Relevance
“…Values followed by letters between parentheses show the originals means. Dousseau et al 2011, Baskin & Baskin 2014, Zucareli et al 2015, Gomes et al 2016. The presence of light (8 h) in the alternating temperature condition was likely not responsible for the onset of the germination process, since the substrate used (paper roll) is not recommended for light-sensitive seeds (Brasil 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Values followed by letters between parentheses show the originals means. Dousseau et al 2011, Baskin & Baskin 2014, Zucareli et al 2015, Gomes et al 2016. The presence of light (8 h) in the alternating temperature condition was likely not responsible for the onset of the germination process, since the substrate used (paper roll) is not recommended for light-sensitive seeds (Brasil 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the occurrence of significant interactions between temperature and substrate (p < 0.05), indicating that there is at least one combination of these two factors that optimizes germination percentage. Bassaco et al (2014), Gomes, Oliveira, Ferreira, and Batista (2016) and Silva et al (2017) also reported a significant interaction between temperature and substrate for seed germination of other forest species of the Atlantic Forest.…”
Section: Resultsmentioning
confidence: 82%
“…The Myrtaceae family has several native fruit species widely distributed in Brazil (GOMES et al, 2016). An example is the species Acca sellowiana (O. Berg) Burret, popularly known as "goiaba-serrana" native to southern Brazil.…”
Section: Introductionmentioning
confidence: 99%